THE IMPACT OF JOB STRESS AND WORKLOAD ON E-COMMERCE EMPLOYEES JOB SATISFACTION WITH SOCIAL SUPPORT AS AN INTERVENING VARIABLE - Muhammad Rafi Dhia (Jurnal Humaniora & Sosial Sains, 2024)
This study uses a quantitative approach and survey method to investigate the impact of job stress and workload on job satisfaction among e-commerce employees in Indonesia, with social support as an intervening variable. The research sampled 100 full-time employees selected through purposive sampling. Data were collected via a validated and reliable questionnaire and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with SmartPLS 4 software. Path analysis was employed for hypothesis testing, assessing significance with p-values and T-values. Results indicate that job stress significantly affects job satisfaction (p < 0.005, T = 3.033) and social support (p < 0.005, T = 4.750). Workload also significantly impacts job satisfaction (p < 0.005, T = 5.169) and social support (p < 0.005, T = 3.800). Social support significantly influences job satisfaction (p < 0.005, T = 5.169). Mediation analysis shows that job stress and workload have significant indirect effects on job satisfaction through social support (p < 0.005, T = 6.633 for job stress; p < 0.005, T = 5.569 for workload). These findings highlight the importance of social support in mitigating the effects of job stress and workload on job satisfaction.